Judicialization of access to orthopedic surgical procedures in a specialized institute in traumatology and orthopedics of the Unique Health System (SUS) (Research, Society and Development, 2022)
The present study aims to evaluate the litigation of orthopedic surgical procedures within the Brazilian healthcare system from demands presented to the National Institute of Orthopedics and Traumatology (INTO), from January 2014 to December 2017. The study was a documentary research, with an exploratory, descriptive and retrospective nature, complemented by the examination of lawsuit requirements, medical records and the local hospital management software system. Out of the 1,886 lawsuits identified, 1,175 had direct relation to healthcare and 109 demanded orthopedic surgical procedures. Out of the demanded cases, most were requested by the Federal Public Defender’s Office. Amongst the requesters, most of them were male, with 60 years of age or older and retired, with hip and/or knee arthroplasty corresponding 47,7% out of the requests. Out of the total, 86,2% of the requests demanded were proceeded. The time median, upon the lawsuit arrival at INTO, ranged from 8 to 30 days to patients previously consulted at INTO and from 8 to 23 days for those coming from other institutions and without any internal medical record. The study showed how lawsuit litigation for surgical procedures may lead not only to a negative impact on an institution’s patient care management but also on the patient’s surgical waiting list. It is important to ponder the excluding factor of such activity, which ends up reallocating assets not considering the principle of equity, to demand a surgical procedure in one patient whilst others, who are in similar or even worse conditions to those benefited from lawsuits, have got to wait longer on the waiting line.